Syirik dan Dampaknya Bagi Kehidupan Manusia - Sitha Nurcahaya Dewi; Jelita Pinasti; Dwi Rahmadani; Muhammad Aldi Rahman; Wismanto Wismanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Shirk is the act or belief of associating Allah SWTwith something or someone in worship or his attributes. In Islam, shirk is considered a major sin that has negative consequences for humans. Allah SWTsays: